(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This study aims to analyze errors made by Russian-speaking Korean language learners in using the Korean adverbial case particle ’에(e)’ and to identify the causes of these errors. By examining the difficulties faced by learners due to differences between the Russian and Korean adverbial case systems, this research seeks to derive systematic error patterns through frequency analysis and error type analysis. The results of this study are expected to provide foundational data for developing effective Korean language education methods for Russian-speaking learners, and furthermore, to have significant implications for Korean language education as a foreign language in general. In particular, it can provide practical assistance in developing educational content and methods for the accurate use of the adverbial case particle ’에(e)’.